Crucial Readings in Functional Grammar - Anstey, Matthew; Mackenzie, J. Lachlan (Functional Grammar Series FGS ;, 2012)
Crucial Readings in Functional Grammar is an invaluable resource to anyone working in Functional Grammar, student and scholar alike. It contains important articles that have led to new avenues of research in the theory, each concluded with a short paragraph with suggestions for further research. The book also contains an introduction to current Functional Grammar theory by the editors.